Amazon Fire phone the missing manual - Gralla, Preston (O'Reilly, 2015)
Unleash the powers of the Amazon Fire phone with help from technology guru Preston Gralla. Through clear instructions and savvy advice, this fast-paced, engaging guide shows you how to make the most of Fire phone's innovative features - including Firefly, Dynamic Perspective, one-handed gestures, and integration with Amazon Prime.